2022
DOI: 10.1136/heartjnl-2022-320897
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and cardiovascular mortality across the spectrum of aortic stenosis

Abstract: ObjectiveCurrent data regarding the impact of diabetes mellitus (DM) on cardiovascular mortality in patients with aortic stenosis (AS) are restricted to severe AS or aortic valve replacement (AVR) trials. We aimed to investigate cardiovascular mortality according to DM across the entire spectrum of outpatients with AS.MethodsBetween May 2016 and December 2017, patients with mild (peak aortic velocity=2.5–2.9 m/s), moderate (3–3.9 m/s) and severe (≥4 m/s) AS graded by echocardiography were included during outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Epidemiologic studies have shown that diabetes is associated with LV dysfunction in patients with AS. [23][24][25] Moreover, among patients with AS, those with diabetes were shown to have a 2-fold to 3-fold higher risk of death from heart failure, as well as a higher risk of sudden cardiac death. 1,24,26 As T2D is associated with intrinsic impairments in myocardial energy metabolism and coronary microvascular function, [27][28][29][30][31][32][33][34] persistent deficits in the myocardial energetic state and abnormalities in MBF even after AVR may be implicated in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic studies have shown that diabetes is associated with LV dysfunction in patients with AS. [23][24][25] Moreover, among patients with AS, those with diabetes were shown to have a 2-fold to 3-fold higher risk of death from heart failure, as well as a higher risk of sudden cardiac death. 1,24,26 As T2D is associated with intrinsic impairments in myocardial energy metabolism and coronary microvascular function, [27][28][29][30][31][32][33][34] persistent deficits in the myocardial energetic state and abnormalities in MBF even after AVR may be implicated in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, with a relatively small number of events and a short duration of follow-up, the finding that the patients with AS-T2D experienced more clinical events should be interpreted with caution, although it is consistent with the established literature. 1,[23][24][25][26] A larger study with a longer follow-up duration will be required to confirm the significance of the observed clinical outcome differences. In addition, the complexity of the imaging protocol, in particular the MRS, may limit its widespread use.…”
Section: Limitationsmentioning
confidence: 99%
“…Coisne et al add to the body of evidence evaluating cardiovascular outcomes in 820 patients with diabetes (30%) among 2703 patients with mild to severe AS from Northern France 5. The analyses came from a registry with blinded endpoint evaluation.…”
mentioning
confidence: 99%
“…Notwithstanding, the study by Coisne et al 5 reminds the clinician when following the patient with AS that the combination of AS, diabetes, and in many cases also, hypertension does lead to significant cardiovascular morbidity and mortality and should be taken very seriously.…”
mentioning
confidence: 99%
“…In adults with severe aortic stenosis (AS), diabetes mellitus (DM) is associated with an increased risk of cardiovascular mortality. In order to study the effect of DM on clinical outcomes earlier in the disease course of AS, Coisne and colleagues3 studied a cohort of 2703 patients with mild, moderate or severe AS (mean age 76 years, 47% women) of whom 30% had concurrent DM. Over a 2.1 year mean follow-up interval, death occurred prior to aortic valve replacement in 7% and DM was significantly associated with a higher cardiovascular mortality (HR=1.40, 95% CI 1.04 to 1.89; p=0.029), primarily due to death from heart failure or sudden death (figure 2).…”
mentioning
confidence: 99%